Effect of adding sodium lactate and acetic acid on on Verocytotoxin-producing Escherichia coli (VTEC) in red and white meat - Al-Ali, Ammar Haji; Arwaneh, Abdulaziz; Suleiman, Ghiath (Journal of agricultural, environmental and veterinary sciences, 2025)
The aim of this research was to study the effect of sodium lactate and acetic acid on Verocytotoxin-producing Escherichia coli (VTEC) in red and white meat. These bacteria are considered a major cause of some meat-borne diseases and contribute significantly to meat spoilage. The aim was to inhibit the growth of these bacteria to the permissible limit. Meat samples were immersed in a sodium lactate solution at different concentrations (2% and 4%) and acetic acid solution at concentrations (1% and 2%) for 30 minutes. The effect of acetic acid at two different concentrations on these meats was then studied. The results were evaluated after testing the number of bacteria in the meat. The results demonstrated the ability of sodium lactate to inhibit the growth of these bacteria. Samples treated with a 2% sodium lactate solution inhibited these bacteria, while a 4% concentration performed better on these meats. Acetic acid at 1% and 2% concentrations inhibited the growth of E. coli. We conclude from this study that adding 4% sodium lactate can eliminate these bacteria, while acetic acid at 1% and 2% concentrations inhibited the growth of E. coli, which produces a toxin that is toxic to Vero cells. The results showed significant differences at P<0.05. These results confirm that adding these compounds can reduce contamination with these bacteria and thus contribute to public health.